Construction Of The Drilled Shaft Foundations For The Huey Long Mississippi River Bridge, New Orleans - Dan A. Brown (Deep Foundations Institute, 2010)
The foundations at the Huey P. Long Bridge in New Orleans presented special challenges for construction due to the requirements for very deep drilled shafts in the Mississippi River beneath the existing bridge structure. Drilled shafts were constructed to depths of approximately 200ft in alluvial soils using a rotator system with full-length segmental casing, and base grouted to improve axial resistance. This paper describes the design and construction of the work platform to provide access to the restricted-access site beneath the existing bridge, the approach used to construct the drilled shafts, and the results of a load test program to verify the axial resistance.